Health Professionals’ Responses to Patient Gift-Giving - Shahriar Mousavinejad; Erfan Mahjoob Khaligh; Mirsaeed Attarchi; Kourosh Delpasand (Journal of Iranian Medical Council, 2026)
Background: Healthcare professionals› acceptance of gifts poses ethical dilemmas, potentially biasing clinical decisions and eroding public trust. The aim of this study is to investigate the prevalence, motivations, and responses to gift-giving among healthcare staff. Methods: An analytical cross-sectional study was conducted at Razi Hospital, Rasht, from January to June 2024. Convenience sampling was used to recruit physicians, nurses, and residents. A valid questionnaire was used to collect data. The validity was ensured through expert panel review and pilot testing, and reliability was confirmed by calculating Cronbach’s alpha which showed acceptable internal consistency. After obtaining informed consent, participants completed questionnaires detailing gift types, timing, motivations, and responses to gift offers. Results: This study involved 97 healthcare workers, with 53.6% being male and an average age of 43.6 years. The majority were nurses (67%). The most common type of gift received was goods (45.6%), usually given before hospitalization (67%). Gifts were refused mainly due to rules against accepting them (42.3%), lack of personal need (5.2%), or fear of potential consequences (6.1%). Among the 45 participants (46.39%) who accepted gifts, 53.3% received cash, 24.4% goods, 17.8% services, and 4.5% influence. Most gift recipients were nurses (71.2%), with the remainder being other medical staff (28.8%), all indicating gratitude as the primary reason for acceptance. Conclusion: Many healthcare staff accept gifts, often cash, driven by patient gratitude. These findings underscore the need for clear policies and ethical training to mitigate conflicts of interest and maintain public trust in healthcare